Gustatory and olfactory dysfunctions in hospitalised patients with COVID-19 pneumonia: a prospective study - Felipe García; Ana González Cordón; Pedro Puerta-Alcalde; Celia Cardozo; Carolina Garcia-Vidal; Marta Bodro; Isam Alobid; Juan Ambrosioni; Jhon Rojas; Alexy Inciarte; Berta Torres; Alex Soriano; et al. (BMJ Open)
Importance Identifying undetected clinical signs is imperative in the prevention of SARS-CoV-2.Objective To establish the prevalence of clinical gustatory and olfactory dysfunctions in patients with COVID-19 pneumonia. Clinical outcomes and recovery rates associated with gustatory and olfactory dysfunctions were also assessed.Design A prospective study was performed in 80 patients admitted to Hospital Clínic of Barcelona (Spain) for COVID-19 pneumonia. Patients were re-evaluated in the ward daily until discharge. Gustatory and olfactory dysfunction symptoms were retrospectively collected from emergency room (ER) charts after first assessments. Follow-up was performed in telemedicine consultation.Setting The single-centre study was performed in a hospitalisation ward at a university hospital.Participants Consecutive patients meeting hospitalisation criteria for COVID-19 pneumonia were eligible. Study exclusion criteria were patients who could not speak, had previous gustatory and olfactory dysfunctions or whose PCR tests for SARS-CoV-19 were negative.Interventions Systematic assessment of gustatory and olfactory symptoms with standardised questions.Outcome(s) Prevalence of gustatory and olfactory dysfunctions in patients with COVID-19 pneumonia.Results Of the 80 study subjects, 62.5% were male and the median age was 57 years. Half of the cohort (n=40) presented with comorbidities. The prevalence of chemosensitive disorder was 73.8% (n=59) (95% CI: 63.8 to 83.8), although self-reported symptoms were recorded in only 26.3% (n=21) of patients in the ER. Gustatory and olfactory dysfunctions were observed in 58.8% (n=47) and 55% (n=44) of cases, respectively. They were also the first symptoms in 25% (n=20) of patients. Anosmia was associated with ageusia, OR: 7, 95% CI: 2.3 to 21.8, p=0.001). No differences in clinical outcomes were observed when patients with and without gustatory and olfactory dysfunctions were compared. Recovery rates were 20% (n=10) and 85% (n=42) at days 7 and 45, respectively.Conclusion The prevalence of gustatory and olfactory dysfunctions in COVID-19 pneumonia was much higher than in self-report. Presence of gustatory and olfactory dysfunctions was not a predictor of clinical outcomes.